A report for the Royal College of general practitioners (Portuguese Journal of Family Medicine and General Practice, 2005)
I feel most grateful for the sequence of occasions when I have been invited to witness the progress of generalist primary care in Portugal - and for the exceptional generosity I have encountered. I have seen notable developments over twenty-five years and gained many friends.